Contribution of E-Marketing for the Income Generation in Travel Agencies of Nepal - Humagain, Parbat (Journal of Business and Social Sciences Research, 2019)
The major objective of this study is to examine the relationship between internet marketing usage and its contribution for the income generation in travel agencies of Nepal. The research is descriptive in nature and is an applied research. The research is based on quantitative data. The populations for the study are the basically owners, chairman and managers of travel agencies and the sample size consists of 120 respondents. The data for the research are collected through primary source of data collection method that includes questionnaire. The research is also carried out with the help of secondary data as we need to study related theories to make research more insightful. Descriptive as well as inferential analyses have been done for the data to be analyzed. Frequency tables are analyzed through SPSS 16.0 and are used for descriptive analysis. Chi- Square test, and Hypothesis Testing (t-test) and Correlation have been done for inferential analysis. The data analysis is of cross sectional in nature. The survey resulted that, there is a strong correlation between internet marketing uses and increase in return on equity, increase in average sales volume and general increase in company income in travel agencies of Nepal. There exists a strong correlation between increases in return on equity and reduction in operating costs, increase average sales volume and general increase in profit margin of the business. From the research, it is noted that there are several benefits obtained from incorporating the internet in marketing strategies. Therefore, the travel agencies should utilize more internet marketing methods and try to incorporate the internet in all their marketing strategies in order to fully enjoy the benefits of internet marketing. Since internet coverage is increasing through the introduction of mobile internet, marketing on the internet becomes a critical factor concerning the company income.